An Exploratory Clinical Trial for Idiopathic Osteonecrosis of Femoral Head by Cultured Autologous Multipotent Mesenchymal Stromal Cells Augmented with Vascularized Bone Grafts - Aoyama, Tomoki (Mary Ann Liebert, Inc., 2014)
Idiopathic osteonecrosis of femoral head (ION) is a painful disorder that progresses to collapse of the femoral head and destruction of the hip joint. Although its precise pathology remains unknown, the loss of blood supply causing the loss of living bone-forming cells is a hallmark of the pathophysiology of osteonecrosis. Transplantation of multipotent mesenchymal stromal cells (MSCs) is a promising tool for regenerating the musculoskeletal system. The aim of the present study was to assess the safety and efficacy of transplantation of cultured autologous bone marrow-derived MSCs mixed with β-tricalcium phosphate (β-TCP) in combination with vascularized bone grafts for the treatment of advanced stage ION in a clinical trial. Ten patients with stage 3 ION were enrolled in this study. Autologous bone marrow-derived MSCs were cultured with autologous serum, and cells (0.5–1.0×10(8)) were transplanted after mixing with β-TCP granules in combination with vascularized iliac bone grafts. Patients were assessed 24 months after treatment. The primary and secondary endpoints were progression of the radiological stage and changes in bone volume at the femoral head, and clinical score, respectively. Nine of ten patients completed the protocol, seven of whom remained at stage 3, and the remaining two cases progressed to stage 4. The average bone volume increased from 56.5±8.5 cm(3) to 57.7±10.6 cm(3). The average clinical score according to the Japan Orthopaedic Association improved from 65.6±25.5 points to 87.9±19.0 points. One severe adverse event was observed, which was not related to the clinical trial. Although the efficacy of cell transplantation was still to be determined, all procedures were successfully performed and some young patients with extensive necrotic lesions with pain demonstrated good bone regeneration with amelioration of symptoms. Further improvements in our method using MSCs and the proper selection of patients will open a new approach for the treatment of this refractory disease.